Evaluation of pyrite and pyrrhotite in concretes - A. P. Marcelino; J. M. Calixto; A. G. Gumieri; M. C. Ferreira; C. L. Caldeira; M. V. Silva; A. L. Costa (Revista IBRACON de Estruturas e Materiais)
ABSTRACT It is well known that aggregate characteristics can intensively interfere in concrete behavior especially when sulfides are presented in the aggregates. The lack of consensus to content limit value of these deleterious sulfur compounds in concrete structures for dams has motivated several investigations worldwide. Within this scenario, this work presents a methodology to evaluate the presence of pyrite and pyrrhotite in concretes produced with aggregates containing sulfides. For the study, rock samples from the Irapé hydroelectric power plant area in Minas Gerais (Brazil) were used. This plant was built in a geological site where the rock presented sulfide levels of at least 3%. These rock samples were first ground and then used as aggregates in mortars, which were, during almost one year, subjected to three different exposed conditions: temperature of 23° ± 2°C and relative humidity of 95 to 100%; calcium hydroxide solution diluted in water kept at two different temperatures: room temperature and 50° C. The presence and amount of pyrrhotite were obtained from a leaching process of the material (aggregate or mortar) in a solution of hydrochloric acid. This procedure allowed also the evaluation of the pyrite content. The results showed that the amount of pyrite has remained virtually constant over time in the three exposure situations. This finding indicates that sulfur limits in aggregates should be set according to the type of iron sulfide presented and not solely by the total amount of sulfur.